THE INFLUENCE OF WORK ENVIRONMENT AND WORK DISCIPLINE ON WORK ACHIEVEMENT WITH EMPLOYEE POSITION PROMOTION AS AN INTERVENING VARIABLE AT THE AIRPORT AUTHORITY OFFICE REGION II MEDAN - Rangga Prasetyo; Kiki Farida Ferine; Toyib Daulay (Lafadz Jaya Publisher, 2023)
The purpose of this study was to see the effect of the work environment and work discipline on work performance with promotion as an intervening variable. Medan Region II Airport. The research population consisted of 96 employees and all populations were sampled and the sample technique used was saturated samples. The research model used was Path analysis and the research calculation tool used Smart PLS 3.3.3. Data collection techniques used were questionnaires and surveys. Based on the results of the research that has been done and the data analysis as explained in the previous chapter, the following conclusions are conveyed from the results of the research as follows: Work Discipline has a positive and significant effect on Work Performance. Work Discipline has a positive and insignificant effect on Promotion. The work environment has a positive and insignificant effect on work performance. The work environment has a positive and significant effect on promotion. Promotion has no significant negative effect on work performance. Work Discipline has an indirect effect on work performance through insignificant negative promotion. The work environment has an indirect effect on work performance through insignificant negative promotion.